Uji Aktivitas Sitotoksik Ekstrak Etanol Anggur Laut (Caulerpa racemosa) dengan Metode BSLT (Brine Shrimp Lethality Test): Cytotoxic Activity Test of Sea Grape (Caulerpa racemosa) Ethanol Extract with BSLT (Brine Shrimp Lethality Test) Method - Sri Hainil; Ghalib Syukrilah; Rastria Meilandra; Daniel Kurniawan (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Indonesia, especially in the Riau Islands has abundant marine biological natural resources. So that it can be used as the basic ingredient of a search for medicinal or medicinal materials. One of them is the caulerpa racemosa sea grape type from the green algae group which contains a variety of secondary metabolites with bioactive compounds that are cytotoxic to kill cancer cells. This study aims to determine the cytotoxic activity of sea grape ethanol extract originating from Terih Village, Nongsa Beach, Riau Islands. The method had been used the BSLT method with Artemia Salina Leach larvae as the test animal. The results showed that the ethanol extract of terih beach sea grape, Nongsa contains alkaloid compounds, flavonoids, saponins and phenolics. The results of the cytotoxic test of sea grape ethanol extract showed results with an LC50 value of 2,154 ppm. From this study, it can be concluded that the ethanol extract of sea grapes is not cytotoxic with a value of LC50 > 1000 ppm so it does not have the potential to be a basic ingredient for anticancer testing.